Characterization of Nevirapine Resistance Mutations in Women With Subtype A Vs. D HIV-1 6–8 Weeks After Single-Dose Nevirapine (HIVNET 012) - Eshleman, Susan H.; Guay, Laura A.; Mwatha, Anthony; Brown, Elizabeth R.; Cunningham, Shawn P.; Musoke, Philippa; Mmiro, Francis; Jackson, J. Brooks (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2004)
To compare the number and type of nevirapine (NVP) resistance mutations detected in Ugandan women with subtype A vs.D HIV-1 infection after single-dose NVP prophylaxis.In the HIVNET 012 trial, a higher rate of NVP resistance (NVPR) was seen in women with subtype D than A after single-dose NVP. In this study, the number and type of NVPR mutations detected 6–8 weeks after NVP were compared in women with subtypes A vs. D.Plasma samples were available for 282 (92%) of 306 women who received NVP in HIVNET 012. Samples were analyzed with the ViroSeq HIV-1 Genotyping System (Applied Biosystems, Foster City, CA). Subtyping was performed by phylogenetic analysis of pol region sequences. Results were obtained for 279 women, including 147 with subtype A, 98 with subtype D, 6 with subtype C, and 28 with recombinant HIV-1. NVPR mutations were detected in 70 (25%) of 279 women. NVPR was more common in women with subtype D vs. A (35.7 vs. 19%, P = 0.0035). Complex patterns of NVPR mutations were detected in both subtypes. Among women with NVPR, 43% of women with subtype A and 46% of women with subtype D had 2 NVPR mutations. The mean number and pattern of NVPR mutations detected in women with subtypes A and D were similar. This study confirms a higher rate of NVPR in women with subtype D than A and further defines the pattern of NVPR mutations that emerge 6–8 weeks after single-dose NVP prophylaxis in these subtypes.
Keywords: HIV-1, nevirapine, drug resistance, subtype, Uganda